(untitled) (Journal of Dhaka Medical College, 2021)
Aim: The study was carried out to see the Serum Bilirubin, ALT, AST and Alkaline Phosphatase as liver function in liver cirrhotic patient. Method: The study was carried out among 50 well-compensated patients of cirrhosis of liver irrespective of their age, sex, residence & income group. Patient was randomly selected while they were hospitalized in Dhaka Medical College Hospital, Sir Salimullah Medical College & Mitford Hospital and Bangabandhu Sheikh Mujib Medical University. Result: Serum Bilirubin, AST, ALT and Alkaline Phosphatase level were done in 50 (fifty) cirrhotic patient out of whom 38 were male and 12 were female. Mild to severe level of serum bilirubin were documented in 50% patients. Two-fold and fourfold rise of ALT were formed in 48% and 10% cirrhotic patient respectively. Similar pattern of rise of AST also shown in 50% cirrhotic patient. Alkaline Phosphatase value was normal in 92% patient and of 08% two-fold rise of Alkaline Phosphatase Alkaline Phosphatase. J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 190-191